INTEGRATING ARTIFICIAL INTELLIGENCE INTO MEDICAL EDUCATION IN PAKISTAN: AN URGENT REFORM AGENDA - Yousafzai, Abdul Wahab; Fatima Saeed Khan,; Shawaf Naeem, (Journal of Ayub Medical College Abbottabad, 2026)
Although AI has become integral to medical training internationally, its uptake within Pakistan’s medical-education system is minimal. Few institutions offer structured AI exposure, leaving graduates underprepared for data-driven clinical practice. Integrating AI literacy, ethical principles, and governance into undergraduate curricula is now essential to modern clinical competence.Integrating these components would enhance diagnostic reasoning, safeguard patient safety and align Pakistan’s medical training with global standards.